Evaluation of Hecke–Rogers series and expansions of the rank function - Bradley-Thrush, J. G. (The Ramanujan journal, 2024)
A formula is established for the evaluation of double series of Hecke–Rogers type in terms of theta functions and Appell–Lerch functions. This formula is similar to others obtained previously by Hickerson and Mortenson, and by Mortenson and Zwegers. It is applied to the rank function, leading to an expansion closely analogous to two of Garvan’s double series identities. Several identities involving third-order mock theta functions are obtained as special cases.